Standardization of Suitable Soil and Water Conservation Measures Using Remote Sensing and GIS for Small Watersheds - Kumar, Virendra; Singh, R S; Singh, P K; Singhvi, B.S.M (Journal of Agricultural Engineering, 2007)
The study was conducted to standardize the suitable interventions adaptable for arable and non-arable land in a small watershed of agro climate zone IV A of Southern Rajasthan. Availability of water resource is limited in the area because of scanty and uneven rainfall pattern. Hence, proper management of rainfall by identifying the appropriate soil and water conservation measures adaptable in the area is important for the region. Remote sensing data were used from satellite imagery IRS IC LISS III and the database including soil map, slope map, soil depth map and land use map were prepared for the area under study applying GIS. Based on the database, Puerto Rico terrace, contour vegetative bund and contour bund for arable land and V-ditch, contour trenches and staggered trenches for non arable land were identified as major interventions that can be implemented in the small watersheds. Measuring and then analyzing the runoff and sediment yield from various interventions, their appropriate/standard dimensions have been identified and recommended that can be adopted in the area.